21st century management leadership and innovation in the thought economy - Lindgren,Mats. (Basingstoke Palgrave Macmillan, 2012)
Explores the changing business landscape of the 21st century and what it means for organizations. The author presents a new model for how to think about and handle the complex world of business from a managerial and innovative perspective with tips and tools for motivating and engaging your organization, clients and customers.
Includes index.
Keywords: Leadership